Treatment Outcome of Using Guided Bone Regeneration for Bone Augmentation for the Placement of Dental Implants – A Systematic Review - Deepak Chandrasekaran; Ravindran Chinnaswami; N. Malathi; N. D. Jayakumar (Journal of Pharmacy and Bioallied Sciences)
Aim: The objective of this review is to evaluate the treatment outcome differences between guided bone regeneration (GBR) and other techniques of bone augmentation for the placement of dental implants. Materials and Methods: This review was performed by two reviewers electronically on the PubMed and Cochrane database for articles published between 1990 and 2023. Only randomized clinical trials (RCTs) and prospective studies were included. Studies involved patients who have been treated with dental implants with simultaneous or previously performed GBR. Results and Discussion: A total of 470 studies were identified after implementing the search strategy across the different databases. The results that have been reported may also be influenced by these factors. Conclusion: After a careful evaluation of the limited evidence included in studies, it can be concluded that GBR is a stable and effective technique of bone augmentation when compared to block grafting and distraction osteogenesis.